Local chemical bonding and structural properties in Ti_{3}AlC_{2} MAX phase and Ti_{3}C_{2}T_{x} MXene probed by Ti 1s x-ray absorption spectroscopy - Martin Magnuson; Lars-Åke Näslund (Physical Review Research, 2020)
The chemical bonding within the transition-metal carbide materials MAX phase Ti_{3}AlC_{2} and MXene Ti_{3}C_{2}T_{x} is investigated by x-ray absorption near-edge structure (XANES) and extended x-ray absorption fine-structure (EXAFS) spectroscopies. MAX phases are inherently nanolaminated materials that consist of alternating layers of M_{n+1}X_{n} and monolayers of an A-element from the IIIA or IVA group in the Periodic Table, where M is a transition metal and X is either carbon or nitrogen. Replacing the A-element with surface termination species T_{x} will separate the M_{n+1}X_{n}-layers forming two-dimensional (2D) flakes of M_{n+1}X_{n}T_{x}. For Ti_{3}C_{2}T_{x} the T_{x} corresponds to fluorine (F) and oxygen (O) covering both sides of every single 2D M_{n+1}X_{n}-flake. The Ti K-edge (1s) XANES of both Ti_{3}AlC_{2} and Ti_{3}C_{2}T_{x} exhibit characteristic preedge absorption regions of C 2p-Ti3d hybridization with clear crystal-field splitting while the main-edge absorption features originate from the Ti 1s→4p excitation, where only the latter shows sensitivity toward the fcc-site occupation of the termination species. The coordination numbers obtained from EXAFS show that Ti_{3}AlC_{2} and Ti_{3}C_{2}T_{x} are highly anisotropic with a strong in-plane contribution for Ti and with a dynamic out-of-plane contribution from the Al monolayers and termination species, respectively. As shown in the temperature-dependent measurements, the O contribution shifts to shorter bond length while the F diminishes as the temperature is raised from room temperature up to 750 °C.